Factors associated with the mental health status of pregnant women in China: A latent class analysis - Pei, Yifei; Chen, Qian; Zhang, Ying; He, Chenlu; Wang, Jingjing; Tang, Jie; Hou, Hao; Zhu, Ziqing; Zhang, Xunbao; Wang, Wei (Frontiers in Public Health, 2023)
Background: Prenatal mental health is a neglected public health issue, which might place pregnant women at a higher risk for mental disorder. The purpose of this study was to investigate the influencing factors of prenatal mental disorder and provide a scientific basis to guide pregnant women’s mental health. Methods: The study sample comprised 973 women with first pregnancy during the second trimester and the third trimester stages who underwent obstetric outpatient checkups at Maternal and Child Health Hospital in Huai’an were recruited in the survey from July to December 2017. The Chinese mental health scale (CMHS) was used to assess mental health. We used the Chi-square test to compare the rate of class with different demographic variables, a latent class analysis to identity psychological symptoms, and the multiple logistic regression to examine whether the demographics predicted class membership. Results: The Chi-squared tests results showed that participants reported differently in perinatal period (2=6.35, P=0.04), marriage satisfaction (2=15.8, P0.001), in-law relationship (2=29.43, P0.001), friend relationship (2=24.81, P0.001), basic diseases (2=8.04, P=0.02) and take birth control pills (2=8.97, P=0.01) have different probabilities of being classified. Three latent classes were identified: high symptoms group (6.89%), moderate symptoms group (20.56%), and low symptoms group (72.56%). Pregnant women in the third trimester (OR=1.83, 95% CI: 1.04-3.25, P=0.04), with lousy in-law relationships (OR=2.82, 95% CI:1.45-5.51, P=0.002), had a lousy friend relationship (OR=3.17, 95% CI: 1.31-7.71, P=0.01) and had basic diseases (OR=1.70, 95% CI: 1.00-2.90, P=0.04) tended to be classified to the high symptoms group than the low symptoms group. Those who have a bad friend relationship (OR=2.15, 95% CI: 1.08-4.28, P=0.03), and take birth control pills (OR=1.51, 95% CI: 1.08-2.11, P=0.02) were more likely divided into moderate symptoms group compared to low symptoms group. Conclusions: The factors of pregnant women’s mental health status include perinatal period, marriage satisfaction, in-law relationship, friend relationship, basic diseases, and taking birth control pills. In order to ensure the smooth progress of pregnancy and promote the physical and mental health of pregnant women, psychological screening and psychological intervention should be strengthened.